Recent Trends in the Clinicopathological Features of Thyroid Nodules in Pediatric Patients: A Single Tertiary Center Experience over 25 Years - Cheong-Sil Rah; Won Woong Kim; Yu-mi Lee; Won Gu Kim; Dong Eun Song; Ki-Wook Chung; Seong Chul Kim; Suck Joon Hong; Tae-Yon Sung (International Journal of Endocrinology)
Background. The trends in pediatric patients having thyroid nodules have not been well evaluated. Here, we analyzed the clinicopathological features of the children who have presented with thyroid nodules at our center over several decades in order to determine a change of trend. Materials and Methods. We analyzed 215 pediatric patients who had undergone a thyroidectomy between 1990 and 2014 at our single tertiary center. The clinicopathological features were analyzed according to age, sex, and the year of diagnosis. Results. The most common reason for hospital admission was a palpable anterior neck mass (76.7%). The males in the patient cohort were younger than the females (13 vs. 15 years old, p<0.05). The female patients increased from 50.0% to 83.0% with age (p<0.05). The rate of malignancy did not increase with age (p<0.05). However, the malignancy rate was higher in the more recently seen patients (23.8% during the early study period and 86.8% in the late study period; p<0.05). Conclusion. Following a thyroidectomy in children with thyroid nodules, there was no change in the rate of detection of thyroid cancer over time with age, although the detected frequency of malignancy has increased in more recent patients. Therefore, early thyroid nodule detection for malignant screening is likely to be required for pediatric patients in the near future.